Penerapan Knowledge Sistem Informasi Penjaminan Mutu Fakultas Berbasis Web Di FTI-UKSW - Christopher, William; Widiasari, Indrastanti Ratna (Journal of Information System and Informatics, 2021)
Information technology is one of the assets of a company or organization that is important for its development, with the rapid development of technology today, technology must always be updated. One of the roles of information technology is the application of knowledge management. Knowledge Management is a system that is able to improve and manage knowledge information in companies or agencies that apply knowledge management. In this study, it focuses on implementing a knowledge management system in the Quality Assurance of the Faculties at Satya Wacana Christian University. This research is based on the fact that PMF institutions still use manual methods in data archiving, the purpose of this study is to design a web application that is useful for archiving PMF data to make it more effective and efficient. In this study, the KMS (Knowledge Management System) is applied, and uses the Knowledge Management System Life Cycle method which consists of several process stages consisting of infrastructure evaluation, KMS design analysis and development, and evaluation at the final stage. The result of this research is a useful data archiving web application for PMF. It is hoped that PMF will be more efficient in data archiving.